EFL Pre-Service Teachers' Experiences Using a Digital Multimodal Composing Framework to Design Digital Storytelling Books - Navila, Ais; Rochsantiningsih, Dewi; Drajati, Nur Arifah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
In the twenty-first century, educators must have competency in technology integration in language classrooms for language learning, which should receive much attention in teacher training programs and professional development. Furthermore, integrating digital multimodal composing into English language teaching through digital storytelling books might assist teachers in building their technological abilities. Therefore, this study aims to investigate the pre-service teachers' experiences in designing digital storytelling books with digital multimodal composing frameworks. The present study adopted narrative inquiry to elucidate pre-service teachers' experiences designing digital storytelling books with multimodal composing framework. This study highlights the experiences of four postgraduate students as pre-service EFL teachers in designing digital books as teaching media. According to the findings, pre-service teachers employ the critical, creative, and technical domains as phases in creating digital storytelling books, which include information from written reflections and interviews. Further research needs to examine the teacher's perceptions of designing digital books as teaching media in real class and students' perceptions when using books designed by the teacher.